Στέφανος Α. Κουμανούδης, Ημερολόγιον 1845-1867. Μεταγραφή Στέφανος Ν. Κουμανούδης, Επιμέλεια-Επιλεγόμενα Άγγελος Π. Ματθαίου, Αθήνα (Ίκαρος) 1990, 222 σ. + 1 πίνακας. - ΠΟΛΙΤΗΣ ΑΛΕΞΗΣ (Μνήμων, 1991)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><span style="font-size: 10.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EL; mso-fareast-language: EL; mso-bidi-language: AR-SA;">Δεν παρατίθεται περίληψη. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>